Post-migration factors and mental health outcomes in asylum-seeking and refugee populations: a systematic review - Gleeson, Christina (Eur J Psychotraumatol, 2020)
The present systematic review examined post-migration variables impacting upon mental health outcomes among asylum-seeking and refugee populations in Europe. It focuses on the effects of post-settlement stressors (including length of asylum process and duration of stay, residency status and social integration) and their impact upon post-traumatic stress disorder, anxiety and depression. Twenty-two studies were reviewed in this study. Length of asylum process and duration of stay was found to be the most frequently cited factor for mental health difficulties in 9 out of 22 studies. Contrary to expectation, residency or legal status was posited as a marker for other explanatory variables, including loneliness, discrimination and communication or language problems, rather than being an explanatory variable itself. However, in line with previous findings and as hypothesised in this review, there were statistically significant correlations found between family life, family separation and mental health outcomes.